Beyond the job description: a new workplace mindset in Malaysia - Mohd Shariff, Sazlin Suhalmie; Mohamad, Masilah (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2025)
“Quiet quitting” refers to employees doing only what their job requires without going beyond, often as a response to burnout, lack of recognition, and blurred work-life boundaries. First popularized on TikTok in 2022, the trend highlights deeper workplace issues, especially in Malaysia where stress levels are high and many feel undervalued. Employees limit extra effort when rewards, promotions, or recognition are lacking, reflecting challenges in engagement, productivity, and organizational culture.